APPLICATION OF ACTIVE LEARNING STRATEGIES USING SERIES IMAGE MEDIA TO INCREASE SKILLS WRITING SIMPLE ON THIRD GRADE STUDENTS IN LEARNING BAHASA INDONESIA IN SDN 031 PELESIRAN BANDUNG CITY - Sri Haryani; Ida Hydrania; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
Application of Active Learning Strategies using Series Media Drawing to Improve Class III Students' Simple Writing Skills in Indonesian Language Learning. This is because the learning strategy is less effective, the media is inadequate, and students have not been able to pour ideas, opinions, or ideas into writing, lack of supporting media in the learning process, and during teacher learning less use of varied learning strategies so that students are less active and feeling bored, writing skills are very lacking.The purpose of this class action research is to find out the increase in student activity and simple writing skills through the application of active learning strategies with the series drawing media in class III SDN 031 Pelesiran. This type of research used classroom action research based on two cycles. Each cycle consists of two meetings, consisting of planning, action, observation, and reflection. The subject of the study was the third grade students of SDN 031 Pelesiran. Data collection techniques were test and non-test techniques. Data analysis through quantitative and qualitative techniques. The conclusion of the study is that active learning strategies with series drawing media can increase student activity and writing skills in writing simple essays.